An outcomes evaluation of the Allan Gray Orbis Foundation’s Fellowship programme - Swingler, Andrew (Organisational Psychology, 2025)
This dissertation presents an outcomes evaluation of the Allan Gray Orbis Foundation's (AGOF) Fellowship Programme, which aims to expand the pool of responsible high-impact entrepreneurs in South Africa to drive economic growth and employment. The programme provides an entrepreneurship education programme focused on developing an entrepreneurial mindset, entrepreneurial intention, and awareness of entrepreneurship as a career among university students. A qualitative research design was used to assess the Fellowship's effectiveness in developing an entrepreneurial mindset, intention and awareness of entrepreneurship as a career, through a structured extracurricular entrepreneurship programme. The Success Case Method (SCM) was employed, using semi-structured interviews to explore participant experiences of the Fellowship programme. Rather than measuring average effect, the SCM focuses on extreme cases of success and non-success to identify key factors influencing outcomes. Owing to recruitment challenges, the SCM approach was adapted to include participants with minimal outcome attainment while maintaining the distinction between success (n=6) and non- success (n=8) cases. Findings indicate that participants across both groups achieved the programme's core outcomes, widely and meaningfully, with notable success in entrepreneurial mindset development, entrepreneurial intention, and increased awareness of entrepreneurship as a career. Additional key outcomes included a strong valuing of socially responsible entrepreneurship and the role of the AGOF community in participant development. Experiential activities and self-reflection were particularly effective in fostering entrepreneurial mindsets, while exposure to a supportive entrepreneurial community and successful entrepreneurs played a crucial role in increasing entrepreneurial intention by reinforcing networking, positive social norms, and peer support. Despite these successes, challenges in achieving academic success were identified, predominantly regarding participants' connection to their university degree and the strength of their relationship with Programme Officers. Programme Officer support emerged as a critical factor in programme retention and success, with disparities in support especially affecting disadvantaged participants struggling with academic demands. The dissertation concludes that the Fellowship is effective in developing a competent entrepreneurial individual by cultivating entrepreneurial mindset and entrepreneurial intention, fostering socially responsible entrepreneurship, and strengthening entrepreneurial networks. Key recommendations to enhance outcomes include expanding the range of tertiary partner institutions and qualifications to align better with the diverse interests and entrepreneurial goals of participants, integrating more practical entrepreneurial experiences to improve engagement, and enhancing real-world applicability in the theoretical curriculum. In addition, targeted support strategies for disadvantaged participants could improve access to and engagement with Programme Officers, programme retention, and programme impact. The study highlights also the value of outcomes attained by non-success participants, both during the programme and post-exit, with recommendations to support their entrepreneurial development better.